Visualization challenges for a new cyber-pharmaceutical computing paradigm - Turner, R.J.; Chaturvedi, K.; Edwards, N.J.; Fasulo, D.; Halpern, A.L.; Huson, D.H.; Kohlbacher, O.; Miller, J.R.; Reinert, K.; Remington, K.A.; Schwartz, R.; Walenz, B.; et al. (IEEE Parallel and Large Data Visualization and Graphics Symposium 2001, 2001)
Celera has encountered a number of visualization problems in the course of developing tools for bioinformatics research, applying them to our data generation efforts, and making that data available to our customers. This paper presents several examples from Celera's experience. In the area of genomics, challenging visualization problems have come up in assembling genomes, studying variations between individuals, and comparing different genomes to one another. The emerging area of proteomics has created new visualization challenges in interpreting protein expression data, studying protein regulatory networks, and examining protein structure. These examples illustrate how the field of bioinformatics is posing new challenges concerning the communication of data that are often very different from those that have heretofore dominated scientific computing. Addressing the level of detail, the degree of complexity, and the interdisciplinary barriers that characterize bioinformatic problems can be expected to be a sizable but rewarding task for the field of scientific visualization.